Proportion and factors associated with unfavorable outcomes among pulmonary tuberculosis patients in Kelantan: 10 years perspective - Johari, Mohd Khairi Safwan (2024)
Background: Tuberculosis (TB) is a major global health concern and a leading cause of death worldwide. Despite significant efforts to control TB, unfavorable treatment outcomes remain a challenge. Objective: To determine the proportion of unfavorable outcomes and identify factors associated among PTB patients in Kelantan from 2013 to 2022. Methodology: A retrospective cohort study design was employed, utilizing secondary data from the National Tuberculosis Registry (NTBR) in Kelantan. The study included 1,260 PTB patients selected through simple random sampling. Data on sociodemographic characteristics, comorbidities, and clinical features were analysed using descriptive statistics, and univariable, and multivariable logistic regression analyses. Results: The proportion of unfavorable outcomes among PTB patients was 20.8%. Key factors associated with unfavorable outcomes included positive HIV status (Adjusted OR 5.69, 95% CI: 3.78-8.57, p<0.001), multidrug-resistant TB (MDR-TB) status (Adjusted OR 5.69, 95% CI: 2.40-13.52, p<0.001), and DOTs supervision by family members (Adjusted OR 5.02, 95% CI: 1.73-14.59, p=0.003). Conclusion: The findings highlight significant challenges in managing PTB, particularly among HIV-positive and MDR-TB patients and underscore the importance of professional supervision in DOTs. These insights are crucial for developing targeted interventions to improve PTB treatment outcomes in Kelantan.